The Toxicity Exerted by the Antibiotic Sulfadiazine on the Growth of Soil Bacterial Communities May Increase over Time - Santás-Miguel, Vanesa (Int J Environ Res Public Health, 2020)
The toxicity exerted by the antibiotic sulfadiazine on the growth of soil bacterial communities was studied in two agricultural soils for a period of 100 days. In the short-term (2 days of incubation), the effect of sulfadiazine on bacterial growth was low (no inhibition or inhibition <32% for a dose of 2000 mg·kg(−1)). However, sulfadiazine toxicity increased with time, achieving values of 40% inhibition, affecting bacterial growth in both soils after 100 days of incubation. These results, which were here observed for the first time for any antibiotic in soil samples, suggest that long-term experiments would be required for performing an adequate antibiotics risk assessment, as short-term experiments may underestimate toxicity effects.